2017
DOI: 10.1111/epi.13910
|View full text |Cite
|
Sign up to set email alerts
|

Remission of encephalopathy with status epilepticus (ESES) during sleep renormalizes regulation of slow wave sleep

Abstract: This study provides evidence that alterations of overnight changes of NREM-sleep slow waves during active ESES are reversible when ESES resolves, and that the severity of neuropsychological compromise might be related to the extent of slow wave impairment during ESES. Our findings suggest that analysis of slow waves might serve as a prognostic factor regarding cognitive outcome. ESES may serve as disease model of pathologic slow wave sleep and our results might be expanded to epilepsies with spike wave activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…It has long been postulated that the unfavorable cognitive outcome of EAS disorders is at least partly caused by epileptiform activity during sleep; the analysis of SWS might consequently serve as a prognosis factor for cognitive outcome in EAS patients . As early as the 3rd postnatal week, Grin2a KO mice displayed altered hippocampal LTP, which worsened with time and persisted in adulthood .…”
Section: Discussionmentioning
confidence: 99%
“…It has long been postulated that the unfavorable cognitive outcome of EAS disorders is at least partly caused by epileptiform activity during sleep; the analysis of SWS might consequently serve as a prognosis factor for cognitive outcome in EAS patients . As early as the 3rd postnatal week, Grin2a KO mice displayed altered hippocampal LTP, which worsened with time and persisted in adulthood .…”
Section: Discussionmentioning
confidence: 99%
“…In one child, hydrocortisone treatment normalized both the sleep EEG and overnight performance (another child whose EEG was only partially improved showed no improvement), suggesting that the impairment of sleep homeostasis may be responsible for the lack of memory consolidation. Finally, Boelsterli et al (2017) reduced overnight slope decline of sleep slow waves has been shown to be related to poorer learning during wakefulness also in adult patients with focal epilepsy (Boly et al, 2017).…”
Section: Impaired Synaptic Homeostasis In Esesmentioning
confidence: 96%
“…Based on these data, it has been hypothesized that prolonged, sleep-related focal epileptic activity interferes with sleep slow wave activity, particularly at the site of the epileptic focus, hence disrupting the cortical plasticity processes occurring during sleep that are necessary for learning and memory consolidation of what has been acquired in wakefulness, ultimately resulting in neuropsychological and behavioural disorders (Tassinari and Rubboli, 2006). In fact, some recent reports support this hypothesis, by providing electrophysiological evidence that physiological parameters related to NREM slow-wave activity are impaired in children with ESES and recover after ESES resolution (Bölsterli et al, 2011(Bölsterli et al, , 2017. These concepts, that provide a fascinating pathophysiological explanation linking the cognitive impairment to the sleep-related exaggerated epileptic activity that characterize ESES, are efficaciously conveyed by the eponym "Penelope syndrome" in which the 'cognitive threads' (neuronal networks) that are weaved during the day are unravelled (by continuous "spiking") during the night (Tassinari et al, 2009 None of the authors have any conflict of interest to declare.…”
Section: Encephalopathy Related To Status Epilepticus During Slow Slementioning
confidence: 99%